2005
DOI: 10.1016/j.visres.2005.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive TMS over posterior STS disrupts perception of biological motion

Abstract: Biological motion perception, the recognition of human action depicted in sparse dot displays, is supported by a network of brain areas including the human posterior superior temporal sulcus (pSTS). We have used repetitive transcranial magnetic stimulation (rTMS) to temporarily disrupt cortical activity within the pSTS and subsequently measured sensitivity to biological motion. Sensitivity was measured for canonical (upright) point-light animations and for animations inverted 180 deg, a manipulation that rende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
180
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(193 citation statements)
references
References 57 publications
11
180
1
1
Order By: Relevance
“…The function and structure of these regions are associated with biological motion perception (11,15,16,20,(41)(42)(43)(44)(45) and their role in biological motion perception has been confirmed in several TMS studies (15,16). In light of this finding, these data permit a stringent comparison between the performance of our ventral patients and that of the brain-damaged patients with lesions to L-pSTS or L-vPMC (the two "critical" lesion groups).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The function and structure of these regions are associated with biological motion perception (11,15,16,20,(41)(42)(43)(44)(45) and their role in biological motion perception has been confirmed in several TMS studies (15,16). In light of this finding, these data permit a stringent comparison between the performance of our ventral patients and that of the brain-damaged patients with lesions to L-pSTS or L-vPMC (the two "critical" lesion groups).…”
Section: Resultssupporting
confidence: 60%
“…It is unclear, however, whether all of these brain areas contribute causally to the perception of biological motion. Neuropsychological studies in patients and transcranial magnetic stimulation (TMS) studies in normal observers have identified several motion-sensitive areas as critical for biological motion perception, including the posterior superior temporal sulcus (pSTS) and ventral premotor cortex (vPMC) (11,(15)(16)(17), given that a sustained or transient lesion to these regions impairs biological motion perception. However, whether form-sensitive regions in the ventral "form" visual pathway [for example, the extrastriate body area (EBA) (18)(19)(20) in the lateral occipital cortex], which are consistently activated in response to biological motion in neuroimaging studies, play a critical role in biological motion perception remains unknown.…”
mentioning
confidence: 99%
“…Our results suggest that phi 1 reflects the inhibition of the mirror-neuron and/or the enhancement of intrinsic premotor activity, whereas phi 2 reflects the enhancement of the mirror-neuron system and/or the inhibition of intrinsic premotor activity. Potential sources for the centroparietally located phi complex include areas reported to belong to the human mirror-neuron system, in particular parietal areas and the superior temporal sulcus (4,5,9,10,17,(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). The presence of a complex formed by two distinct peaks is an unusual spectral feature of human EEG.…”
Section: Discussionmentioning
confidence: 99%
“…Striate and extrastriate cortex stimulation was conducted in the same testing session, with stimulation sessions separated by 30 minutes since 15 minutes is generally considered to be the duration of rTMS effects elicited by similar stimulation parameters [Grossman et al, 2005]. The order of stimulation was counter balanced across participants.…”
Section: Testing Sessionmentioning
confidence: 99%